The Comparison of Customer Relationship Management (Crm) in Czech Small and Medium Enterprises According to Selected Characteristics in the Years 2015, 2010 and 2005 - Halina Starzyczná; Pavlína Pellešová; Michal Stoklasa (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2017)
The aim of the article is to present the results of the research in 2005 and 2015, respectively 2010, in the field of Customer Relationship Management (CRM). The subject of the research is CRM knowledge, CRM definition preference, customer contact level, and CRM results. The object of the research are the SMEs in the Moravian‑Silesian Region. A method of comparison of selected characteristics was used. Starting point is a brief theoretical discussion based on selected studies, including a brief genesis of research. Recent primary research using questionnaire survey addressed 736 respondents. Comparing the results of the research confirmed the growth of CRM skills between 2010 and 2015. In 2015, the first place in the preferences of the definition of CRM won the option A, meaning the creation of lasting relationships with customers, which delivers long‑term value to both parties to the relationship. The share of respondents who voted for it, was higher than in 2005. To compare the level of contact with customers, 4 ways of contacting them were selected. Adverse developments showed up for the customer records, higher was its randomness, which was not expected. More sophisticated ways of contacting customers confirmed a positive change, though not very significant. The most important result in 2005 and 2015 was the increase in the number of loyal customers, which contributes to the growth of profitability. In the end of the article, hypothesis about the relationship of the size of SMEs and CRM knowledge is confirmed by using logistic regression, and premises are verified about the comparison of results in various years. It turns out that the CRM can be beneficial for SMEs, so it should be implemented in its management system.